Kewajiban Transparansi Informasi Halal Pada Platform Digital Shopee Food - Btr, Mhd Alawik; Zulham (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the obligation to provide transparent information regarding halal features on digital platforms, particularly Shopee Food, to facilitate consumers in selecting healthy and halal food. The research employs an empirical legal method, encompassing observations and document analysis of digital platforms and relevant regulations. The findings indicate that information on product halal status is crucial for Muslim consumers in Indonesia. Digital platforms such as Shopee Food and GoFood have a responsibility to provide halal information features to help consumers choose food that complies with Islamic law. However, many platforms have yet to fulfill this obligation, leading to information asymmetry that may result in adverse selection, where consumers unknowingly purchase non-halal products due to a lack of clear information. The weakness of the current regulations lies in the lack of effective supervision and law enforcement, creating uncertainty for consumers. Therefore, stricter regulations and greater transparency in providing halal information on digital platforms are necessary to ensure Muslim consumer rights and establish a fair and trustworthy trade ecosystem. As a comparison, countries like Malaysia have implemented more comprehensive and effective regulations for halal product oversight, which could serve as a reference for Indonesia in improving its regulatory system.